2020
DOI: 10.1002/jez.2430
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐ and time‐dependent effects of an immune challenge on fish across biological levels

Abstract: Due to global changes, fish are increasingly exposed to immune challenges associated with disease outbreaks in aquatic ecosystems. Adjustments in physiology and behavior are generally critical to maintaining homeostasis after an immune challenge, but there is limited knowledge on the specific thresholds and dynamics of responses across levels of biological organization in fish. In this study, we tested how different concentrations of an antigens mixture (phytohemagglutinin and lipopolysaccharide) affected inna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 98 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…For example, researchers have shown that red colobus monkeys infected with ringworm are lethargic, groom less, and copulate less [Ghai et al, 2015], and that deworming vervet monkeys of gastrointestinal parasites significantly increases their propensity for social interaction [Chapman et al, 2016]. In zebrafish, infection with LPS decreases swimming and drastically reduces social preference [Kirsten et al, 2018;Petitjean et al, 2021]. Finally, in a series of studies by Schall and colleagues, it was demonstrated that malaria infection in western fence lizards decreases aggression, social displays, and social dominance [Schall and Dearing, 1987;Schall and Houle, 1992;Dunlap and Schall, 1995].…”
Section: Social Changes In Sickness Behaviorsmentioning
confidence: 99%
“…For example, researchers have shown that red colobus monkeys infected with ringworm are lethargic, groom less, and copulate less [Ghai et al, 2015], and that deworming vervet monkeys of gastrointestinal parasites significantly increases their propensity for social interaction [Chapman et al, 2016]. In zebrafish, infection with LPS decreases swimming and drastically reduces social preference [Kirsten et al, 2018;Petitjean et al, 2021]. Finally, in a series of studies by Schall and colleagues, it was demonstrated that malaria infection in western fence lizards decreases aggression, social displays, and social dominance [Schall and Dearing, 1987;Schall and Houle, 1992;Dunlap and Schall, 1995].…”
Section: Social Changes In Sickness Behaviorsmentioning
confidence: 99%
“…These factors may explain the lack of clear differences observed in SSI between our groups vs. those found in Binning et al (2018). Spleen enlargement alone may not be an accurate measure to characterize the occurrence of an immune response given the large amongindividual variation that exists among treatments (Petitjean et al 2021) We found altered immune gene expression in fish injected with the two highest doses of LPS (50mg kg -1 and 100mg kg -1 ) and with the lowest one (3mg kg -1 ). Responses to immune stimulants are dose and time dependent.…”
Section: Immune Stimulation Effect On the Spleen Somatic Index And Ge...mentioning
confidence: 80%
“…23,24 The overproduction of ROS could conceivably entail host immunosuppression and severe oxidative damages since the immune response is a costly physiological activity when initiated against foreign microorganisms (non-self entities) or pathogenic processes. 25,26 From this perspective, supplementation of carotenoids for a well-integrated antioxidant system is imperative for enhanced stress tolerance and immunity in cultured animals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as potent singlet oxygen quenchers, carotenoids can potentially halt the toxic effects of reactive oxygen species (ROS) generated during mounting host defence activities without raising the associated costs of immunity 23,24 . The overproduction of ROS could conceivably entail host immunosuppression and severe oxidative damages since the immune response is a costly physiological activity when initiated against foreign microorganisms (non‐self entities) or pathogenic processes 25,26 . From this perspective, supplementation of carotenoids for a well‐integrated antioxidant system is imperative for enhanced stress tolerance and immunity in cultured animals.…”
Section: Introductionmentioning
confidence: 99%